Proposal of the Spanish Socialist Labour Party - International Federation of Trade Unions; Azorín Izquierdo, Francisco, 1885-1975
011-0076-001 PRIVATE AND CONFIDENTIAL For the Joint Meeting of the L.S.I, and the I.F.T.U. in Paris on June 24th, 1937. PROPOSAL OF THE SPANISH SOCIALIST PARTY The Spanish Socialist Labour Party, following upon the suggestion made at the meeting of the L.S.I, amd the I.F.T.U. held at Geneva on June 17th, with a view to stating its demands with regard to the international war to which its national soil is subjected, upholds and declares: That the moral solidarity towards our cause, which has been manifested on many occasions by the members and leaders of the aforementioned Internationals, and also the resolutions of London, (March 3rd, 1937), and Geneva (June 17th, 1937), recognising the failure of the control system, require that the following action should be undertaken : 1. To bring pressure to bear by all possible means and without delay, upon the Governments, members of the League of Nations, in order that in accordance with the pact, they assist the Spanish Government to recover its political and territorial independence. 2. To enforce the return to commercial liberty so that the Spanish Government - whose legitimacy is beyond dispute - may acquire the necessary arms for the defence of its territory and its rights. 3. To make the unquestioned obligations of solidarity towards our cause, incumbent upon all the members and all the responsible organisations affiliated to the internationals. Geneva, June 20th, 1937 For the Spanish Socialist Labour party. FRANCISCO AZORIN. 292/946/11/76